Monoclonal and Polyclonal Antibodies Specific for Foot and Mouth Disease Virus Type A and Type O VP1 - Cho, Jin Gu (Mary Ann Liebert, Inc., 2012)
The foot and mouth disease virus (FMDV) is an RNA virus composed of single stranded positive sense RNA. FMDV has been known to infect cloven-hoofed animals, including pigs, cattle, and sheep. FMDV is rapidly spreading outward to neighboring regions, often leading to a high mortality rate. Thus, early diagnosis of FMDV is critical to suppress propagation of FMDV and minimize economic losses. In this study, we report the generation and characterization of polyclonal and six monoclonal antibodies against VP1 through immunoblotting and immunofluorescence microscopy analyses. These VP1 antibodies will be useful as tools to detect serotypes A and O of FMDVs for diagnostic usage.